Is ADHD a way of conceptualizing long-term emotional stress and social disadvantage? - Erlandsson, Soly I.; Hornborg, Christoffer; Sorbring, Emma; Dauman, Nicolas (Frontiers in Public Health, 2022)
Background The prevalent, neuropsychiatric, deficit perspective on children and youth diagnosed with ADHD prohibits a multidimensional approach where socio-economic status, family stress and relationships within the families are relevant factors to examine. Assessments of ADHD through the use of rating scales and short-term interventions may lead not only to overdiagnosis but also to a reductionistic approach in the psychiatric field. This literature review aims to address research outside the prevailing discourse on ADHD as an organic brain dysfunction and broaden the perspectives on children's behavioral difficulties. Methods The articles included in this applied, mixed-method, systematic review includes 26 peer-reviewed articles, both English and French, with a search focus on ADHD in children and youth related to Attachment styles and relationships. Results In the studies reported, researchers approached correlations between ADHD and attachment in different ways, and in most cases, there was a caution to address causality. The role of parents was found to be both buffering and aggravating for the appearance of ADHD. In the French case studies, the diagnosis was conceptualized as a relational phenomenon where the child's behavior was inseparable from family member's suffering. Discussion This review article illustrates how children's difficulties in terms of ADHD symptoms can be addressed through a paradigm where emotional and cognitive dysregulation is understood through psychosocial factors rather than as a neurological condition. In our view, to avoid an overly reductionistic and medicalized approach to children's behavioral difficulties, it is time to reiterate the value of the biopsychosocial perspective. Conclusion Professionals and researchers need to acknowledge that becoming diagnosed with ADHD has a strong connection to economic disadvantage, social status, and familial care. The academic discourse of addressing brain dysfunctions might serve the unintended purpose of masking emotional stress and social disadvantage that manifests across generations. A biopsychosocial approach to ADHD including family, emotional history, and socio-economic issues could imply a lesser focus on medical treatment as a first choice.